2022
DOI: 10.1186/s12889-022-12905-7
|View full text |Cite|
|
Sign up to set email alerts
|

Individual socioeconomic position, neighbourhood disadvantage and mental well-being: a cross-sectional multilevel analysis of mid-age adults

Abstract: Background Socioeconomic disadvantage is associated with mental illness, yet its relationship with mental well-being is unclear. Mental well-being is defined as feeling good and functioning well. Benefits of mental well-being include reduced mortality, improved immune functioning and pain tolerance, and increased physical function, pro-social behaviour, and academic and job performance. This study aims to explore the relationship between individual socioeconomic position (SEP), neighbourhood di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As a result, this may exacerbate preexisting symptoms and cost the healthcare system an additional $3252-$19 363 per patient, annually (Cutler, Fernandez-Llimos, Frommer, Benrimoj, & Garcia-Cardenas, 2018). Furthermore, due to the strong socioeconomic influence on metabolic health (Mohammed et al, 2019) and mental illness (Mann, Heesch, Rachele, Burton, & Turrell, 2022), this may disproportionately increase the risk for cognitive dysfunction among individuals of low socioeconomic status (Wang et al, 2023). Therefore, when cognitive impairments persist despite the use of standard treatments in mood disorder populations, they may exacerbate the burden at both the individual patient and global healthcare level.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this may exacerbate preexisting symptoms and cost the healthcare system an additional $3252-$19 363 per patient, annually (Cutler, Fernandez-Llimos, Frommer, Benrimoj, & Garcia-Cardenas, 2018). Furthermore, due to the strong socioeconomic influence on metabolic health (Mohammed et al, 2019) and mental illness (Mann, Heesch, Rachele, Burton, & Turrell, 2022), this may disproportionately increase the risk for cognitive dysfunction among individuals of low socioeconomic status (Wang et al, 2023). Therefore, when cognitive impairments persist despite the use of standard treatments in mood disorder populations, they may exacerbate the burden at both the individual patient and global healthcare level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, association between the availability of fast-food restaurants in the neighborhood versus obesity measured by body mass index is especially stronger in subgroup with lower monthly household income [65]. Also, residents of the most disadvantaged neighborhood have lower perceived mental health than those in the least disadvantaged neighborhoods, even after adjustment for individual-level socioeconomic position [61]. Individuals' adaptive responses to the challenges of COVID-19 by applying the grit and resilience (among others) are paramount [66,67].…”
Section: Stronger Associations Of Monthly Household Income With Perce...mentioning
confidence: 99%
“…The current study results showed larger impact that lower monthly household income (socioeconomic inequality) has on perceived health status during the COVID-19 pandemic than pre-pandemic era. Poor socioeconomic position of lower household income itself has been associated with lower perceived mental health (mental well-being) [61]. On the contrary, better household wealth quantile is associated with less depressive symptoms by mediation of better healthcare service access and social contact [56].…”
Section: Stronger Associations Of Monthly Household Income With Perce...mentioning
confidence: 99%
“…The original publication of this article contained 2 typo’s in the abstract. The incorrect and correct information is shown in this correction article [ 1 ]. The original article has been updated.…”
mentioning
confidence: 99%